Apología del pueblo chileno : contexto e implicaciones del discurso de Juan Ignacio Molina - Fuenzalida Caro, Catalina (Estudios Humanísticos. Historia, 2009)
Enmarcada en la "Disputa del Nuevo Mundo", la reivindicación del reino de Chile desplegada por el Abate Juan Ignacio Molina en los ensayos sobre su historia natural y civil, basa sus fundamentos en un concepto de cultura que fusiona corrientes intelectuales antiguas y modernas en un pensamiento híbrido, fruto de la cultura jesuita americana en el exilio. Pero a fines del s. XVIII, periodo de definiciones radicales en la historia de pensamiento, esta escuela se mostrará inviable. La incomprensión de este contexto ha instaurado imágenes arquetípicas que dificultan la integración del tema en la historiografía americana y chilena en particular. ABSTRACT: Enclosed in the “Dispute of the New World”, the claim of The Reign of Chile presented by Juan Ignacio Molina abbé, in his essays about natural and civil history, establishes its principles on a concept of culture which joins old and present intellectual currents, putting them together in a hybridist thought, by consequence of the American- Jesuit culture living in exile. However, by the end of XVIII century, a period of clear-cut definitions in the history of thought, this school will show itself as not viable. The incomprehensibility of this context has renewed images as an archetype which makes difficult the integration of the subject in the American historiography and Chilean historiography in particular.